Justice and nature of contract as determinants of abandoned housing projects - Abdul Razak, Dzuljastri; Abdullah, Moha Asri; Mohammad, Mustafa Omar; Olaniyi, Oladokun Nafiu (Universiti Malaysia Sabah, 2016)
This study aims at exploring the perception of stakeholders, particularly the home buyers, about the causes of abandoned housing project (AHP) in Malaysia. In terms of approach, assessing the determinants of AHP could assist in mitigating the effect of AHP in Malaysia. In this study, we employed factor analysis and structural equation modelling (SEM) to achieve the stated objective. The total sample size of the study comprises of 328 respondents that cut across all states in Malaysia. Two main constructs, namely justice and nature of contract are considered in this study. Furthermore, the results of the SEM revealed that lack of justice and weak regulatory system, coupled with the nature of the contract of financing significantly contribute to the problem of AHPs. Hence, it is suggested that fairness in the contract (e.g., risk sharing) and sound regulatory system could help in mitigating the effect of abandoned housing problems. The samples of this study are confined to Malaysians in Selangor and Kuala Lumpur. Further testing of the proposed model across different states is needed to determine the generalisability of this study’s findings. The current study only examines two factors, which may limit its generalisation. Further testing on other factors is also needed to extend the findings. Concerning the research implications, the results obtained provide directions to policymakers to deal with the issue of AHPs in Malaysia. On the same note, results obtained provide better guidelines to improve the working practice for housing projects among developers. For originality, this study examines the determinants of AHPs in Malaysia. A framework developed captures the importance of justice and nature of the contract to mitigate the AHPs in Malaysia.